Batik stamp training with pesut fish motif at Pela Tourism Village, Kutai Kartanegara, East Borneo - Dita Andansari; Etwin Fibrianie Soeprapto (Community Empowerment, 2022)
Batik is one of the handicrafts that contributes to the national GDP. Apart from being a handicraft sub-sector, batik is also included in the fashion sub-sector. Thus, batik is a commodity that needs to be taken into account and developed so that it can continue to contribute to the national GDP. Some tourist areas in Indonesia make batik as a distinctive souvenir with the characteristics of each motif. Pela as one of the tourist villages in East Kalimantan also wants to develop batik which has a distinctive motif. For this purpose, the Pela Village tourism awareness group, funded by the RASI Conservation Foundation, held a training for batik stamped with the pesut fish motif. The training method used is by delivering theory and direct practice of making stamped batik with a pesut motif. The results obtained from the training, the participants were able to make their own porpoise stamped batik with natural coloring.